2007
DOI: 10.1109/tdei.2007.4401235
|View full text |Cite
|
Sign up to set email alerts
|

On the intrinsic thermal stability in HVDC cables

Abstract: The paper deals with some important aspects of steady state thermal stability in the insulation of HVDC cables. The resistively graded electric field distribution and the temperature distribution, under steady state, in dc cables, are interrelated. The dc conductivity is known to be a function of stress as well as of temperature. Reasonably convincing theories of electric stress and temperature distribution are now available in the literature. Until recently, the thermal runaway was believed, primarily, to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 4 publications
(10 reference statements)
2
14
0
Order By: Relevance
“…9). The dashed line represents the theoretically estimated values of breakdown voltages as plotted against temperature, calculated using [4], [6]. The obtained experimental results are in reasonable agreement with the theoretical estimation proving the mechanism of breakdown in PVC cables as of thermal origin.…”
Section: B Breakdown Voltagesupporting
confidence: 77%
See 2 more Smart Citations
“…9). The dashed line represents the theoretically estimated values of breakdown voltages as plotted against temperature, calculated using [4], [6]. The obtained experimental results are in reasonable agreement with the theoretical estimation proving the mechanism of breakdown in PVC cables as of thermal origin.…”
Section: B Breakdown Voltagesupporting
confidence: 77%
“…Theoretical formulations relating the maximum thermal voltage to the physical and geometrical parameters of the HVDC cable insulation have been proposed in [5]. Much literature is also available detailing causes of thermal instability and runaway [6]. Also, proposals have been made to improve the thermal performance of cable insulation by using polymer nanocomposites to improve dielectric volume resistivity and breakdown strength [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These articles have mainly considered the influence factors of electrical breakdown from view of adding the nano or micro particles. Some researchers also have studied the phenomenon of thermal breakdown [9][10][11][12][13][14][15]. T. Mizutani et al have concluded that a filamentary thermal breakdown occurs in polyimide at high temperature [12].…”
Section: Introductionmentioning
confidence: 99%
“…The other mechanisms do not necessarily need the presence of macroscopic defects. Insulation degradation can however lead to increased losses and possibly hot spots, eventually leading to thermal instability [2], [3]. In section IV, space charge accumulation, a mechanism that does not require the presence of a macroscopic defect is further explored.…”
Section: Degradation and Breakdownmentioning
confidence: 99%